TREATMENT OF PRESSURE ULCERS OF THE SCALP IN DECOMPENSATED HYDROCEPHALY: A CLINICAL CHALLENGE. - Kale, Letitia Bellavesta; Malelak, Elric Brahm; Datusanantyo, Robertus Arian; Ullah, Wajahat; Ali, Ahmed Mohamed Ahmed; Thumar, Dhyey; Kumar, Kundan (Universitas Airlangga, 2023)
Highlights: Studies of pressure injury in hydrocephalus patients are very limited. To determine the staging and diagnosis, clinicians must consider the anatomical location of pressure injury, especially in children. Pressure injury increases the risk of shunt infection in hydrocephalus patients. Abstract: Introduction: A pressure injury is ‘localized injury to the skin and/or underlying tissue usually over a bony prominence, that caused by compression. Multiple studies have demonstrated that age, moisture, immobility, and friction/shear are key risk factors. We report a challenging case of multiple pressure injury over the scalp in hydrocephalus patients. Case Illustration: Three toddlers with Hydrocephalus was consulted due to multiple Pressure Injury over the scalp in the bilateral temporo-parietal and occipital region. After ventriculo-peritoneal shunting (VP-shunt), the wounds were managed in accordance with TIMERS guidelines. Discussion: Pediatric tissues are more susceptible to deformation injuries. Severe skull deformity and macrocephaly are serious problems that may lead to difficulties in head control and child positioning increases the risk of pressure injury. After VP-shunt, wound care is even more challenging since the surgical wound is closely related to pressure injuries. Shunt exposure can be occurred on these patients. According to both examination and intervention of TIMERS guidelines are essential as well as controlling risk factors of pressure injury development. Conclusion: Surgeons should be aware that children with hydrocephalus may experience scalp injuries and changes to their body composition, which challenge the diagnosis and care process.